Does reframing urban policy around wellbeing support carbon mitigation?. Issue 1 (22nd July 2021) - Chapman, Ralph; Howden-Chapman, Philippa
New Zealand ('Aotearoa') is a highly urbanised country with one of the first governments in the world to adopt a wellbeing budget framework. That framework, in combination with the architecture for decarbonisation provided by New Zealand's 2019 'Zero Carbon' Act, means there are now institutional and policy incentives in place, and developing incrementally, to combine the pursuit of wellbeing and decarbonisation. These incentives also align with the outcomes highlighted in the United Nations' Sustainable Development Goals (SDGs). This paper considers the way policy and institutional approaches to carbon mitigation are being linked to wellbeing in three interconnected urban, non-agricultural domains responsible for much of New Zealand's carbon emissions: building, urban form and transport. Looking beyond the current Covid-19 recovery process, emerging evidence is presented to ascertain whether the wellbeing-focused policy approach, with its associated attention to co-benefits, is creating a clear institutional refocusing. In addition, other evidence suggests that New Zealanders see health and wellbeing as improving, at the same time as the country is moving towards the net zero carbon emissions target. Policy relevance: In New Zealand, a new emphasis by the government on wellbeing now provides a powerful policy framing. At the same time, attention to the critical issue of climate change is strongly influencing many aspects of public policy. This paper investigates, for three related economic domains—building, urban form and transport—how the new framing is being manifested in institutions and policy. Attention to co-benefits, highlighting elements of wellbeing, appears to be shifting the policy debate away from economic growth towards a richer set of concerns more relevant to an era in which managing environmental, social and health crises (such as Covid-19), decarbonisation, and housing affordability are more prominent. The paper also outlines a new research programme that measures outcomes from a set of major public housing and urban regeneration investments in terms of wellbeing metrics.